ANALYSING THE INFLUENCE OF WORK-LIFE BALANCE ON WORK ENGAGEMENT WITH A QUALITATIVE APPROACH PT KERETA API INDONESIA - Imanina, Akinda Surya; Nanda Maulidya Rafiqana; Mila Hariani (Jurnal PROFITA : Akuntansi dan Manajemen, 2023)
In the contemporary workplace, the concept of work-life balance has been identified as a significant factor influencing employee engagement. Work-life balance can be defined as a state in which an individual is able to manage their time and energy between work and personal life in a satisfactory manner. One company that would be well-advised to grasp this concept is PT Kereta Api Indonesia, which is engaged in railway transportation. It is well established that employees who have a satisfactory work-life balance are highly engaged. This is due to their capacity to manage their time and energy in a manner that is both efficacious and gratifying. Consequently, it is of paramount importance for this company to give due consideration to and implement the concept of work-life balance in order to enhance employee engagement and foster a more conducive working environment.